Surgical Treatment of a Patient with a Solitary Thyroid Metastasis from Primary Sigmoid Adenocarcinoma: A Case Report and Literature Review - Kohei Yamahara; Toshiaki Moriki; Yuki Katsura; Kana Lee; Satoshi Ikegami (Case Reports in Otolaryngology)
Malignant metastases to the thyroid are rare and even rarer from colorectal cancer (CRC). Most cases of CRC metastasis to the thyroid involve metastases to other organs as well, particularly the liver and/or lung. There are only three reports of CRC metastasizing to the thyroid without involvement of another site. Patients with solitary thyroid metastasis from CRC have a poor prognosis after surgery, whereas resection is beneficial in their counterparts with a solitary liver or lung metastasis. This difference could be the result of delayed diagnosis of thyroid metastasis in patients with CRC, given that postoperative follow-up examination of the thyroid is not routinely performed. Here we describe a patient who was found to have a solitary metastasis of sigmoid cancer to the thyroid on postoperative imaging and has had prolonged disease-free survival after thyroidectomy. Our experience suggests that a low threshold of suspicion is crucial for timely diagnosis of thyroid metastasis from CRC and that resection can improve disease-free survival.